Strategi Pemasaran Produk Sarden Tanira Berbasis Analisis SWOT di PT. SMS Kabupaten Banyuwangi - Dewi Alima Nostalia Suseno (Badan Penerbitan Fakultas Pertanian Universitas Ratu Samban, 2026)
Indonesia as an archipelagic country has great potential in developing the fisheries industry, particularly in processing lemuru fish, which serves as the main raw material for canned sardine products. The intense competition in the canned sardine industry requires every producer to develop effective marketing strategies to survive and grow in the market. This study aims to formulate a marketing strategy for Sarden Tanira products through SWOT analysis to enhance competitiveness and expand market share. The research employed a mixed-methods approach (descriptive qualitative and quantitative) with purposive sampling. Data were collected through interviews, questionnaires, observations, and documentation. The analysis included identifying internal and external factors and quantifying them through IFAS and EFAS matrices to determine the company’s strategic position. The results show that PT. SMS’s main strengths are tasty products with high nutritional content, attractive packaging, preservative-free formulation, and affordable prices; however, the company still faces weaknesses in marketing personnel, delays in raw material supply, and limited dominance in the local market. IFAS = 2.95 and EFAS = 3.10 yielded SWOT matrix coordinates of (X = 0.51; Y = 0.60), placing the company in the SO (Strengths Opportunities) quadrant. Based on these findings, a growth-oriented strategy is recommended, focusing on strengthening brand positioning, optimizing digital channels and e-commerce, implementing customer loyalty programs, enhancing marketing functions (through recruitment or outsourcing of digital marketing), and improving supply chain management through forecasting and supplier diversification. The implementation of these recommendations should be accompanied by performance evaluation using measurable indicators and broader follow-up studies to test the effectiveness of these interventions before full-scale application.